Meningkatkan Kemampuan Membaca Dalam Pembelajaran Jarak Jauh Melalui Presentasi Media Gambar Pada Anak Kelompok B TK Lembaga Tama II Semester II Tahun Ajaran 2020-2021 - Suryaningsih, Any (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
This study aims to improve reading skills in Distance Learning through Image Media Presentation for group B children in TK Lembaga Tama II Semester II for the 2020-2021 academic year. This research is a Classroom Action Research or PTK.The subjects of this study were 16 students of group B TK Lembaga Tama II Sabdodadi Bantul, consisting of 9 boys and 7 girls. The object of this research is the ability to read through the presentation of image media in Distance Learning which includes recognizing and identifying vowels and consonants, combining vowels and consonants, reading simple words or sentences, and writing words and sentences. Data collection methods used for learning are evaluation sheets and documentation in the form of photos of learning activities. The data analysis technique used quantitative and qualitative descriptive analysis techniques.Based on the research results, it can be seen that the children's reading skills have improved. The criteria have not yet developed in pre-action 56%, Cycle I 19%, and Cycle II 5%. On the criteria of starting to develop at 44% pre-action, 44% in Cycle I and 13% in Cycle II. on the criteria of developing according to expectations in pre-action 0%, Cycle I 37%, and Cycle II 57%. Meanwhile, the criteria for developing very well in pre-action were 0%, Cycle I was 0%, and Cycle II had an increase to 25%.